2021
DOI: 10.1177/1057083720984365
|View full text |Cite
|
Sign up to set email alerts
|

Music Teacher Education Program Practices: Preparing Teachers to Work With Diverse Learners

Abstract: Music educators must meet the needs of students with diverse characteristics, including but not limited to cultural backgrounds, musical abilities and interests, and physical, behavioral, social, and cognitive functioning. Music education programs may not systematically prepare preservice teachers or potential music teacher educators for this reality. The purpose of this study was to examine how music teacher education programs prepare undergraduate and graduate students to structure inclusive and responsive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Combined with our finding that one fifth of programs did not require an EGMM course for all PMTs, this result may be particularly troubling. Our results are consistent with Salvador’s (2010) finding that music-specific content on learners with special education needs was typically associated with elementary coursework, as well as Culp and Salvador (2021), who reported that music-specific content on teaching diverse learners was associated with coursework focused on Grades K–5 or K–8. The consistency of this finding across research studies might mean that, in some programs, PMTs could infer that inclusive and responsive practices are only relevant or important in elementary settings.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Combined with our finding that one fifth of programs did not require an EGMM course for all PMTs, this result may be particularly troubling. Our results are consistent with Salvador’s (2010) finding that music-specific content on learners with special education needs was typically associated with elementary coursework, as well as Culp and Salvador (2021), who reported that music-specific content on teaching diverse learners was associated with coursework focused on Grades K–5 or K–8. The consistency of this finding across research studies might mean that, in some programs, PMTs could infer that inclusive and responsive practices are only relevant or important in elementary settings.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to Culp and Salvador (2021) and Salvador (2010), our findings indicated the possibility that PMTs in some programs only learn aspects of inclusive instruction in EGMM courses. Therefore, in addition to our recommendation that music teacher education program professionals carefully consider how they ensure all PMTs are well-prepared to teach children across age-groups, we echo Culp and Salvador’s (2021) suggestion that music teacher educators intentionally thread meaningful discussion and practical information on inclusive teaching practices, such as universal design for learning and culturally responsive pedagogy, throughout every music education course.…”
Section: Implications For Teacher Education and Researchsupporting
confidence: 71%
See 3 more Smart Citations